EFFECT OF TOP MANAGEMENT SUPPORT, SYSTEM QUALITY, AND INFORMATION QUALITY ON SATISFACTION ACCOUNTING INFORMATION SYSTEM USERS IN LEMBAGA PERKREDITAN DESA (LPD) IN UBUD DISTRICT - Sang Ayu Putu Arie Indraswarawati; I Putu Deddy Samtika Putra; Ni Wayan Cahyani (UNHI Press, 2019)
The use of Accounting Information System (AIS) is very helpful in accommodating all the information needed to make an accurate decision. Indicators in determining the good and bad performance of an information system can be seen through AIS user satisfaction and usage. The purpose of this study was to determine the effect of top management support, system quality and information quality on AIS user satisfaction. The sample selection method used was purposive sampling. The research sample was 147 people consisting of administrators, loan officers and savings at 29 Lembaga Perkreditan Desa (LPD) in Ubud Subdistrict. The data in this study is primary data which is the answer from the questionnaire. The regression results show that all variables have a significance of 0,000. It shows that top management support, system quality and information quality have positive influences on Accounting Information System user satisfaction.